Attitude of Thai Dental Practitioners towards the Use of Botulinum Toxin in Dentistry - Laorpipat, Sasi; Fuangtharnthip, Pornpoj; Yuma, Suraphong; Tantipoj, Chanita (International journal of environmental research and public health, 2022)
This study aims to investigate the attitude of Thai dentists towards the use of botulinum toxin (BTX) in dentistry and the associated factors. An online survey was conducted using a semi-structured questionnaire consisting of four parts: demographic data, background knowledge, attitude, and an open-ended question for further suggestions related to BTX usage in dental patients. Multivariate logistic regression was used to analyze factors that affect the decision to use BTX in dentistry, and a content analysis approach was used to describe open-ended suggestion data. We received 444 responses from currently practicing dentists throughout Thailand. Roughly 80% of the participants agreed to the use of BTX in their patients. Most participants were aware that BTX could be used for facial esthetic repairs and bruxism treatment but unaware of other therapeutic benefits. Despite impressively positive attitudes towards BTX use, only 5.9% of the participants had the experience of using BTX in their dental patients. The limit on BTX use is mainly due to the lack of knowledge of related laws and educational resources. In summary, official training courses should be established to promote the safe and legal use of BTX in dentistry in Thailand.